A nova onda de imigrantes em Tete-Moçambique: o caso dos Zimbabweanos (2007-2016) - Tomás Pita Cebola (2018)
The objective of this dissertation is to analyze the new wave of immigrants in the province of Tete - Mozambique through the case of Zimbabwean immigrants. It should be noted that in view of the profound change in the trajectories of traditional migratory movements and their complexity (such as the multiplication of destinations) in the region today, the Mozambican State needs to create laws and framework conditions for populations resulting from immigration flows. Occupying the position of geographic enclave almost completely surrounded by Malawi, Zambia and Zimbabwe, the province of Tete is historically marked as a region of sending emigrants, but in recent times it has also become a destination region, mainly of immigrants from the Zimbabwe, a country with historical ties to the province and which has been facing a deep crisis since the year 2000. Thus, we are interested in reflecting on: who and why these individuals from Zimbabwe and why they emigrate to Tete, broadening the idea centered solely on economic motivations; what conditions they find in Tete and what relations they establish with those originating in Tete. To do so, we cross the largest number of sources available, using both quantitative and qualitative methods. It was used quantitative data from the microdata of the 2007 Mozambican Census and the records of the immigrant workers, the Provincial Directorate of Labor, Employment and Social Security, and also semi-structured interviews with the Zimbabwean immigrants in Tete. Considering the data analyzed, this dissertation argues that there is a multiplicity of factors that contributed to the immigration of Zimbabweans in Tete, highlighting the long tradition of intra-regional mobility in southern Africa, facilitated by relatively porous borders and strong cultural, linguistic and of kinship. On the other hand, the installation of the mega mining projects in Tete, which announced an apparent economic growth of that province, contributed to the increase of the immigration of the neighbors to Tete, in a context of violent and widespread waves of xenophobia in Africa South, (the biggest welcoming of immigrants in the region) against immigrants.